Update on antiretroviral treatment during primary HIV infection. Issue 7 (July 2014) - Ambrosioni, Juan; Nicolas, David; Sued, Omar; Agüero, Fernando; Manzardo, Christian; Miro, Jose M
<x xml:space="preserve">Abstract</x> Primary HIV-1 infection covers a period of around 12 weeks in which the virus disseminates from the initial site of infection into different tissues and organs. In this phase, viremia is very high and transmission of HIV is an important issue. Most guidelines recommend antiretroviral treatment in patients who are symptomatic, although the indication for treatment remains inconclusive in asymptomatic patients. In this article the authors review the main virological and immunological events during this early phase of infection, and discuss the arguments for and against antiretroviral treatment. Recommendations of different guidelines, the issue of the HIV transmission and transmission of resistance to antiretroviral drugs, as well as recently available information opening perspectives for functional cure in patients treated in very early steps of HIV infection are also discussed.